2015
DOI: 10.1104/pp.114.253815
|View full text |Cite
|
Sign up to set email alerts
|

A KNOTTED1-LIKE HOMEOBOX Protein Regulates Abscission in Tomato by Modulating the Auxin Pathway  

Abstract: A gene encoding a KNOTTED1-LIKE HOMEOBOX PROTEIN1 (KD1) is highly expressed in both leaf and flower abscission zones. Reducing the abundance of transcripts of this gene in tomato (Solanum lycopersicum) by both virus-induced gene silencing and stable transformation with a silencing construct driven by an abscission-specific promoter resulted in a striking retardation of pedicel and petiole abscission. In contrast, Petroselinum, a semidominant KD1 mutant, showed accelerated pedicel and petiole abscission. Comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 48 publications
10
76
0
3
Order By: Relevance
“…The 2-thiobarbituric acid method [55] and TTC method [12] were used to measure the MDA content and root activity respectively. Phytohormones were extracted, purified and measured according to previously the reported methods [53,56].…”
Section: Measurement Of Enzyme Activities and Mda And Phytohormone Comentioning
confidence: 99%
“…The 2-thiobarbituric acid method [55] and TTC method [12] were used to measure the MDA content and root activity respectively. Phytohormones were extracted, purified and measured according to previously the reported methods [53,56].…”
Section: Measurement Of Enzyme Activities and Mda And Phytohormone Comentioning
confidence: 99%
“…In addition, KNOX proteins are involved in other hormonal signaling pathways. KNOX change the abundance of proteins associated with auxin transporter signaling components to regulate abscission in tomato (Ma et al, 2015). Rice HOMEOBOX 1 (OSH1) represses the brassinosteroid phytohormone pathway through activation of brassinosteroid catabolism genes (CYP734A2, CYP734A4, and CYP734A6) and then arrests the growth of the SAM (Tsuda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PIN proteins are transporters of the hormone auxin that maintain auxin homeostasis in the plant and, thus, deliver positional information in many developmental processes. Interestingly, KNOX genes participate in the late stages of abscission in A. thaliana (Shi et al ., ) and S. lycopersicum (Ma et al ., ). An historical model of leaf blade abscission, based on exogenous application of auxin on debladed P. vulgaris leaf explants, proposed an auxin gradient in the leaf blade during abscission (Addicott & Lynch, ; Addicott et al ., ), whereas recently it was shown that the auxin signalling is a prerequisite for floral abscission in Arabidopsis (Basu et al ., ).…”
Section: Discussionmentioning
confidence: 97%